CAMPURAN KOMPOS TANDAN KOSONG KELAPA SAWIT DENGAN KOMPOS LCC DAN PUPUK PTERHADAP SERAPAN P DAN PRODUKSI TANAMAN SORGUM (Sorghum bicolor L) - Siagian, Delima Rubintang; Sjofjan, Jurnawaty; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine the interaction between EFB compost with LCC compost and P fertilizer mixture on P uptake and production of sorghum. The research was carried out by experiments using a completely randomized design (CRD), which consists of 2 factors and 3 replications. The data obtained were statistically analyzed using analysis of variance and tested further to the test of Duncan's New Multiple Range test (DNMRT) at 5% level. The observations made are analysis P uptake, age out panicle, harvesting, number of branches panicle, number of seeds per panicle, grain weight per panicle, weight of 1000 seeds, the results per plot and the ratio of seed and straw. The results of P fertilizer treatment mixture of 60 kg/ha and EFB compost1.25 tonnes/ha with LCC compost 3.75 tonnes/ha is that it can increase the uptake of P sorghum at 42 DAT is 9.98 mg. The highest yield was obtained on treatment with the proceeds 882.72 g/plot (2.45 tonnes/ha). Keywords: Compost, EFB, LCC, P, Sorghum